Detailed Analysis of Apoptosis and Delayed Luminescence of Human Leukemia Jurkat T Cells after Proton Irradiation and Treatments with Oxidant Agents and Flavonoids. (3rd July 2012) - Baran, Irina; Ganea, Constanta; Privitera, Simona; Scordino, Agata; Barresi, Vincenza; Musumeci, Francesco; Mocanu, Maria Magdalena; Condorelli, Daniele F.; Ursu, Ioan; Grasso, Rosaria; Gulino, Marisa; Garaiman, Alexandru; et al.
Abstract : Following previous work, we investigated in more detail the relationship between apoptosis and delayed luminescence (DL) in human leukemia Jurkat T cells under a wide variety of treatments. We used menadione and hydrogen peroxide to induce oxidative stress and two flavonoids, quercetin, and epigallocatechin gallate, applied alone or in combination with menadione or H2 O2 . 62 MeV proton beams were used to irradiate cells under a uniform dose of 2 or 10 Gy, respectively. We assessed apoptosis, cell cycle distributions, and DL. Menadione, H2 O2 and quercetin were potent inducers of apoptosis and DL inhibitors. Quercetin decreased clonogenic survival and the NAD(P)H level in a dose-dependent manner. Proton irradiation with 2 Gy but not 10 Gy increased the apoptotic rate. However, both doses induced a substantial G2 /M arrest. Quercetin reduced apoptosis and prolonged the G2 /M arrest induced by radiation. DL spectroscopy indicated that proton irradiation disrupted the electron flow within Complex I of the mitochondrial respiratory chain, thus explaining the massive necrosis induced by 10 Gy of protons and also suggested an equivalent action of menadione and quercetin at the level of the Fe/S center N2, which may be mediated by their binding to a common site within Complex I, probably the rotenone-binding site.